4.2 - Addition, Multiplication & Transposition of Matrices - Shams El-Din El-Fouly; Siddharth Misra (My University)
In this lesson you'll learn about addition, multiplication and transposition to two matrices in addition to what a Principle Diagonal, Principal anti-diagonal, identity and unit matrices

This file is part of a series of video lectures for Dr. Siddharth Misra’s class, Numerical Methods for Engineering Computation, at the University of Oklahoma. The video series demonstrates how to develop numerical methods using C++, Python, and MATLAB and shows the codes and methods being developed from the scratch. Students are encouraged to develop their own codes along with the videos. The series is numbered as follows:

1.1 – 1.8.

2.1 – 2.3

3.1 – 3.7

4.1 – 4.7

5.1 – 5.5

6.1 – 6.4

7.1 – 7.5

8.1 – 8.4